Dystocia due to a tumor-like mass prior to delivery: Double uterus - Rozza Bejarano, Carlos (2011)
Introduction: An abnormal shaped uterus is a cause of dystocia. Uterine shape abnormalities influence both pregnancy and labor outcome, leading to complications during this latter period. Clinical case report: This is the case of a 23-year old woman, full-term pregnant, seen during labor period. Delivery became dystocic and her uterus was found to be approximately 45º rotated to the right; also, a smaller additional non-pregnant uterus was found in the left side, its size was 12 x 10 cm. Non pregnant uterus acted like a tumoral mass exerting pressure upon both shoulders of the fetus, with led to dystocia because of a prolonged expulsive stage, which ended up in a false intarpartum uterine rupture.